From Bright to Brightness: Mastering the Management of Bilateral Congenital Cataracts - Imelda, Eva; Nuzhatuddin, Fatimah; Jannah, Siti Rain; Adev, Sarra Mutiara; Adev, Alya Mutiara; Toshniwal, Navneet Shamsundar (Indonesian Journal of Case Reports, 2023)
Congenital cataract is the leading cause of vision loss in newborns and children, and it is caused by an opacity of the eye's lens that occurs at birth or within the first few months of life. Congenital cataracts may develop as unilateral or bilateral. Around 50% of cases of it are considered as idiopathic. A 4-month-old boy was brought by his parents to the Department of Pediatric Ophthalmology and Strabismus in RSUD dr. Zainoel Abidin Banda Aceh with a chief complaint of a white spot on the patient’s right eye. The spot had appeared since birth and became more visible when he was 2 months old. The patient's overall condition was good. Both eyes' visual acuity was blink reflex. The ocular pressure in both eyes was normal. An ophthalmologic examination revealed a fully clouded right eye lens and aphakia in the left eye. The patient had undergone cataract surgery on his left eye on September 6th, 2023. He was diagnosed with Congenital Cataract Oculus Dexter (OD) and Aphakia Oculus Sinister (OS) before surgery. The patient underwent right eye cataract surgery with aspiration irrigation (AI), Primary Posterior Capsulotomy (PPC), and Anterior Vitrectomy (AV) without Intraocular Lens (IOL) implantation within the next two weeks.  Following the surgery, the patient's visual function improved to fix and follow the object, the pupils looked round in both eyes, aphakia, and no membrane development. The patient was prescribed glasses for optical rehabilitation.